Measurement-based ray-tracing models calibration in urban environments (2012)
This paper investigates the effect produced on the accuracy of the estimate of path loss in an outdoor environment in order to adjust the permittivity values for building wall, building roof and street floor by using a full 3D ray-tracing system. Due to the complexity of a real situation, estimation of path loss using the ray-tracing method is generally assumed one or three large classes of homogeneous materials to represent the building walls, building roofs and street floors in order have a viable model of the 3D environment. However, in a real case, an outdoor environment consists of many buildings and streets made of heterogeneous materials. We analyze the behavior of the statistical variation of standard deviation, correlation coefficient and the average error between the values of estimated and measured path loss data when considering various values of permittivity of these three classes.